## Integers

## Exercise – 6.2

**Ex 6.2 Question 1.**

**Using the number line write the integer which is:**

**(a) 3 more than 5**

**(b) 5 more than -5**

**(c) 6 less than 2**

**Solution:**

(a) 3 more than 5

Moving 3 steps from 5. Hence, 3 more than 5 = 8

(b) 5 more than -5

Moving 5 steps from -5. Hence, 5 more than -5 = 0

(c) 6 less than 2

Moving 6 steps from 2. Hence, 6 less than 2 = -4

(d) 3 less than -2

Moving 3 steps from -2, Hence,3 less than -2 = -5

**Ex 6.2 Question 2.**

**Use number line and add the following integers:**

**(a) 9 + (-6)**

**(b) 5 + (-11)**

**(c) (-1) + (-7)**

**(d) (- 5) + 10**

**(e) (-1) + (-2) + (-3)**

**Solution:**

**Ex 6.2 Question 3.**

**Add without using number line:**

**(а) 11 + (-7)**

**(b) (-13) + (+18)**

**(c) (-10) + (+19)**

**(d) (-250) + (+150)**

**(e) (-380) + (-270)**

**(f) (-217) + (-100).**

**Solution:**

(a) 11 + (-7) = 4

(b) (-13) + (+18) = 5

(c) (-10) + (+19) = 9

(d) (-250) + (+150) = -100

(e) (-380) + (-270) = -650

(f) (-217) + (-100) = -317

**Ex 6.2 Question 4.**

**Find the sum of:**

**(a) 137 and -354**

**(b) -52 and 52 .**

**(d) -312, 39 and 192**

**(d) -50, -200 and 300**

**Solution:**

(a) 137 and -354

(137) + ( -354) = (137) + (-137) + (-217) [∵ (137) + (-137) = 0]

= 0 + (-217) = (-217)

(b) -52 and 52

(-52) + (+52) = 0 [ ∵ (-a) + (+ a) = 0]

(c) -312, 39 and 192

(-312) + (+ 39) + (+192)

= (-231) + (- 81) + (+39) + (+192)

= (-231) + (-81) + (+ 231)

= (-231) + (+ 231) + (-81)

[∵ (-a) + (a) = 0]

= 0 + (- 81) = – 81

(d) – 50, -200 and 300

(-50) + (-200) + (+ 300)

= (-50) + (-200) + (+200) + (+100)

= (-50) + 0 + (+100)[∵ (-a) + (+ a) = 0]

= (-50) + (+100)

= (-50) + (+50) + (+ 50)

= 0 + (+ 50) = 50 [ ∵ (-a) + (+ a) = 0]

**Ex 6.2 Question 5.**

**Find the sum of:**

**(a) (- 7) + (-9) + 4 + 16**

**(b) (37) + (-2) + (-65) + (-18)**

**Solution:**

(a) (- 7) + (-9) + 4 + 16

= (-7) + (-9) + 4 + (+ 7) + (+ 9)

= (-7) + (+7) + (-9) + (+9) + 4

= 0 + 0 + 4 = 4 [∵ (-a) + (a) = 0]

(b) (37) + (-2) + (-65) + (-8)

= (+37) + (-75)

= (+37) + (-37) + (-38)

= 0 + (-38) = (-38) [∵ (-a) + (+a) = 0]